Prenatal Ultrasound Diagnosis of a Cyst of the Oral Cavity: An Unusual Case of Thyroglossal Duct Cyst Located on the Tongue Base - E. Rodríguez Tárrega; S. Fuster Rojas; R. Gómez Portero; S. Roig Boronat; G. Pérez Martínez; J. Zamora Prado; A. Perales Marín (Case Reports in Obstetrics and Gynecology)
We describe a case of a lingual thyroglossal duct cyst diagnosed prenatally by ultrasound at 26 weeks of gestation. The follow-up ultrasound scans revealed no changes in the cyst measurement. Surgical treatment was performed without any complication 72 hours after delivery with good results.